Applications of GO/OA‐POSS Layer‐by‐Layer self‐assembly nanocoating on flame retardancy and smoke suppression of flexible polyurethane foam. (21st July 2021) - Jia, Pengfei; Cheng, Wenhua; Lu, Jingyi; Yin, Zhenting; Xu, Zhoumei; Cheng, Liang; Qiu, Yong; Qian, Lijun; Hu, Yuan; Hu, Weizhao; Wang, Bibo
Abstract: Flexible polyurethane foam (FPUF) is extremely flammable and will release a large number of toxic fumes during the combustion process, which brings great safety hazards. Therefore, a binary hybrid nanocoating composed of graphene oxide (GO) and octaamino polyhedral oligomeric silsesquioxane (OA‐POSS) is deposited on the surface of FPUF through layer‐by‐layer self‐assembly technology, with the aim of enhance the flame retardancy and smoke suppression properties of the hybrid FPUF. Compared with pure FPUF, the peak heat release rate, the total heat release, the peak smoke production rate and the total smoke release of FPUF@GO/OA‐POSS‐6 is decreased by 67.3%, 28.3%, 65.03% and 42.9%, indicating the hybrid FPUF excellent flame retardancy and smoke suppression properties. Compared with pure FPUF, the tensile strength of FPUF@GO/OA‐POSS‐6 is increased by 42%, and after three times of compression, the compressive strength increases by 83.17% on average. Facts have proved that the hybrid effect between GO and OA‐POSS enhances the flame retardancy, smoke suppressive effects, tensile strength and compressive strength of FPUF.